Intravenous dexamethasone administration during anesthesia induction can improve postoperative nutritional tolerance of patients following elective gastrointestinal surgery: A post-hoc analysis - Tian, Feng; Zhou, Xinxiu; Wang, Junke; Wang, Mingfei; Shang, Zhou; Li, Leping; Jing, Changqing; Chen, Yuezhi (Frontiers in Nutrition, 2023)
Aim: To investigate the effect of intravenous dexamethasone administration on postoperative enteral nutrition tolerance in patients following gastrointestinal surgery. Methods: Based on the previous results of a randomized controlled study to explore whether intravenous administration of dexamethasone recovered gastrointestinal function after gastrointestinal surgery, we used the existing research data from 1-5 days post operation in patients with enteral nutrition tolerance and nutrition-related analyses of the changes in serum indices, and further analyzed the factors affecting resistance to enteral nutrition. Result: The average daily enteral caloric intake was significantly higher in patients receiving intravenous administration of dexamethasone during anesthesia induction than in controls (8.80±0.92 kcal/kg/d vs. 8.23±1.13 kcal/kg/d, P=0.002). Additionally, intravenous administration of 8 mg dexamethasone during anesthesia induction can reduce the changes in postoperative day (POD) 3, POD5, and preoperative values of serological indices, including ΔPA, ΔALB, and ΔRBP (P<0.05). In the subgroup analysis, dexamethasone significantly increased the average daily enteral nutrition caloric intake in patients undergoing enterotomy (8.98±0.87 kcal/kg/d vs. 8.37±1.17 kcal/kg/d, P=0.010) or in female patients (8.94±0.98 kcal/kg/d vs. 8.10±1.24 kcal/kg/d, P=0.019). The changes of serological indexes (ΔPA, ΔALB, ΔRBP) in the dexamethasone group were also significantly different on POD3 and POD5, (P<0.05). In addition, multivariate analysis showed that dexamethasone use, surgical site, and age might influence enteral nutrition caloric tolerance. Conclusion: Postoperative enteral nutrition tolerance was significantly improved in patients receiving intravenous administration of dexamethasone during anesthesia induction, especially in patients following enterotomy surgery, with significant improvements in average daily enteral caloric intake, PA levels, ALB levels, and RBP levels.